2021
DOI: 10.1016/j.arrct.2021.100160
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Movement-to-Music (M2M) Intervention on Physical and Psychosocial Outcomes in People Poststroke: A Randomized Controlled Trial

Abstract: Objective To investigate the effects of a 12-week movement-to-music (M2M) intervention on physical and psychosocial outcomes in people poststroke. Design Two-arm randomized controlled trial. Setting A community-based fitness facility. Participants Participants (N=47) with stroke between 18 and 65 years old were randomized to M2M (n=23) or waitlist control (n=24). Interventions Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…For PWD, reducing secondary health conditions, such as pain and fatigue, is a priority for improving overall health, and several participants stated this as a benefit they received from the program. These benefits are similar to those found in onsite M2M-based programs (22,23).…”
Section: Discussionsupporting
confidence: 79%
“…For PWD, reducing secondary health conditions, such as pain and fatigue, is a priority for improving overall health, and several participants stated this as a benefit they received from the program. These benefits are similar to those found in onsite M2M-based programs (22,23).…”
Section: Discussionsupporting
confidence: 79%
“…Regarding program adherence, we deemed an overall adherence rate of 69% to be acceptable. This determination was based on evidence that adherence rates between 50% and 69% to an on-site 12-week M2M program resulted in improved functional mobility among adults with physical disabilities [ 30 , 54 ]. Nevertheless, adherence was strong during the first 2 weeks of the program and declined gradually throughout weeks 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…The SIT intervention was adapted from a clinical adult exercise program, referred to as movement-to-music [ 84 ]. The program originated from a clinical efficacy trial that demonstrated improvements in lower extremity function and fatigue among adults with mobility disabilities [ 84 ]. The success of movement-to-music led to its implementation in larger confirmatory trials among adults with disabilities [ 85 - 87 ].…”
Section: Methodsmentioning
confidence: 99%